Special Issue “Electric, Magnetic, and Electromagnetic Fields in Biology and Medicine: From Mechanisms to Biomedical Applications: 2nd Edition” - Stefania Romeo; Anna Sannino (Bioengineering)
Electric, magnetic, and electromagnetic fields (EMFs) are widely used in everyday life, as well as in specific occupational environments and clinical settings [...]